Masonry Structures: Between Mechanics and Architecture - Aita, Danila; Pedemonte, Orietta; Williams, Kim.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Birkhäuser, 2015)
This book provides an overview of state of the art research in the mechanics of masonry structures. It continues the series Between Mechanics and Architecture, initially launched in 1995 from the collaboration of several renowned scholars, including Edoardo Benvenuto and Patricia Radelet-de Grave.   The contributions in this volume represent the main approaches to the complex topic of masonry structures. In addition to historical studies, the mechanical behavior of masonry arches and structures is studied using different approaches (structural analysis, limit analysis, elastic analysis, plasticity, mathematical approaches, etc.), at times difficult to reconcile, at others intertwined and complementary.   Readers will have the opportunity to compare different theoretical lines of inquiry and thus explore new horizons of research.   Contributions by: Danila Aita Andrea Bacigalupo Riccardo Barsotti Stefano Bennati Antonio Brencich Mario Como Salvatore D’Agostino Luigi Gambarotta Jacques Heyman Santiago Huerta Massimiliano Lucchesi Patricia Radelet-de Grave Elio Sacco Miroslav Šilhavý Anna Sinopoli Piero Villaggio Nicola Zani.
Danila Aita, Orietta Pedemonte: Preface -- Stefano Bennati: In Memory of Piero Villaggio -- Salvatore D’Agostino: Between Mechanics and Architecture: the Quest for the Rules of the Art -- Mario Como: Statics of Historic Masonry Structures. An Essay -- Jacques Heyman: Equilibrium Analysis -- Anna Sinopoli: A Semi-analytical Approach for Masonry Arch Dynamics -- Andrea Bacigalupo, Antonio Brencich and Luigi Gambarotta: On the Statics of the Dome of the Basilica of S. Maria Assunta in Carignano, Genoa -- Patricia Radelet-de Grave: The Panthéon’s Stability already questioned by Pierre Patte in 1770 -- Danila Aita, Riccardo Barsotti, Stefano Bennati: Limit and Non-linear Analysis of Masonry Arches: some Contributions and Solutions -- Elio Sacco: Some Aspects in the Statics of Masonry Arches -- Massimiliano Lucchesi, Miroslav Šilhavý, Nicola Zani: A Direct Approach to Membrane Reinforced Bodies -- Piero Villaggio: The Thrust of an Elastic Soil of Variable Density against a Rigid Wall -- Index of Names.
Keywords: Mathematics; History; Mathematics in Art and Architecture; History of Mathematical Sciences